DFT Study on the Substituent Effect of Anticancer Picoline-Diazido-Pt(IV) Compounds - Mu, Meilin; Gao, Hongwei (Frontiers in Oncology, 2022)
The geometric structure of azido Pt(IV) compounds containing picoline was calculated by using density functional theory(DFT) at the LSDA/SDD level. The ESP distribution shows the possible reaction sites of the compounds. In addition, the frequency calculation results assigned the infrared spectra of these compounds, and specified important stretching and bending vibrations. The HOMO-LUMO energy gaps of these compounds are also calculated to explain the charge transfer of the molecules. The distribution of Mulliken charges and natural atomic charges of these atoms is also calculated. Natural bond orbital(NBO) analysis explains the intramolecular interactions and their electron density.